Transcatheter MitraClip repair alters mitral annular geometry – device induced annular remodeling on three-dimensional echocardiography predicts therapeutic response - Jiwon Kim; Maria Chiara Palumbo; Omar K. Khalique; Lisa Q. Rong; Razia Sultana; Mukund Das; Jennifer Jantz; Yasfumi Nagata; Richard B. Devereux; Shing Chiu Wong; Geoffrey W. Bergman; Robert A. Levine; et al. (Cardiovascular Ultrasound, 2019)
Abstract Background Echocardiography (echo) is widely used to guide therapeutic decision-making for patients being considered for MitraClip. Relative utility of two- (2D) and three-dimensional (3D) echo predictors of MitraClip response, and impact of MitraClip on mitral annular geometry, are uncertain. Methods The study population comprised patients with advanced (> moderate) MR undergoing MitraClip. Mitral annular geometry was quantified on pre-procedural 2D transthoracic echocardiography (TTE) and intra-procedural 3D transesophageal echocardiography (TEE); 3D TEE was used to measure MitraClip induced changes in annular geometry. Optimal MitraClip response was defined as ≤mild MR on follow-up (mean 2.7 ± 2.5 months) post-procedure TTE. Results Eighty patients with advanced MR underwent MitraClip; 41% had optimal response (≤mild MR). Responders had smaller pre-procedural global left ventricular (LV) end-diastolic size and mitral annular diameter on 2D TTE (both p ≤ 0.01), paralleling smaller annular area and circumference on 3D TEE (both p = 0.001). Mitral annular size yielded good diagnostic performance for optimal MitraClip response (AUC 0.72, p < 0.01). In multivariate analysis, sub-optimal MitraClip response was independently associated with larger pre-procedural mitral annular area on 3D TEE (OR 1.93 per cm2/m2 [CI 1.19–3.13], p = 0.007) and global LV end-diastolic volume on 2D TTE (OR 1.29 per 10 ml/m2 [CI 1.02–1.63], p = 0.03). Substitution of 2D TTE derived mitral annular diameter for 3D TEE data demonstrated a lesser association between pre-procedural annular size (OR 5.36 per cm/m2 [CI 0.95–30.19], p = 0.06) and sub-optimal MitraClip response. Matched pre- and post-procedural TEE analyses demonstrated MitraClip to acutely decrease mitral annular area and circumference (all p < 0.001) as well as mitral tenting height, area, and volume (all p < 0.05): Magnitude of MitraClip induced reductions in mitral annular circumference on intra-procedural 3D TEE was greater among patients with, compared to those without, sub-optimal MitraClip response (>mild MR) on followup TTE (p = 0.017); greater magnitude of device-induced annular reduction remained associated with sub-optimal MitraClip response even when normalized for pre-procedure annular circumference (p = 0.028). Conclusions MitraClip alters mitral annular geometry as quantified by intra-procedural 3D TEE. Pre-procedural mitral annular dilation and magnitude of device-induced reduction in mitral annular size on 3D TEE are each associated with sub-optimal therapeutic response to MitraClip.